Factors Influencing Resilience among the Students with Visual Impairment in the Special Schools of Tamil Nadu - Raj, M. Maria Antony (International Journal of Psychosocial Rehabilitation, 2020)
Background: The human race in the modern World comprises of people with dissimilarities in many aspects, persons with disabilities are one among them. Inadequate studies on the positive side of children with visual impairment lead to the demand for studies which focus on their strength and potential. Aim: Measuring the resilience and its relationship with other influencing factors was the prime aim of the research. Methods: A descriptive design was adopted for this study. Among the 234 students who were studying higher secondary courses in special schools, 176 students were taken as a sample through a stratified proportionate random sampling technique. The standardized scales used in this study were The Resilience Scale, Multidimensional Scale of Perceived Social Support, Brief COPE, School Environment Inventory and Self-concept Inventory. Results: The findings of the study were that 39.2 per cent had a moderate level of Resilience. More over Perceived social support, Positive coping, Negative coping, Self-concept and School environment all together explained 30 percent of the variance in the level of Resilience. Conclusion: Based on the results obtained through the study, the researcher proposed a few suggestions so that the students with visual impairment can enhance their resilience. The support from the stakeholders would provide sufficient assistance to the students with visual impairment in order to overcome their problems and be successful.